2015
DOI: 10.1002/glia.22957
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic myelin destruction by schwann cells during wallerian degeneration and segmental demyelination

Abstract: As lysosomal hydrolysis has long been suggested to be responsible for myelin clearance after peripheral nerve injury, in this study, we investigated the possible role of autophagolysosome formation in myelin phagocytosis by Schwann cells and its final contribution to nerve regeneration. We found that the canonical formation of autophagolysosomes was induced in demyelinating Schwann cells after injury, and the inhibition of autophagy via Schwann cell-specific knockout of the atg7 gene or pharmacological interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
147
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(157 citation statements)
references
References 40 publications
10
147
0
Order By: Relevance
“…GomezSanchez et al recently demonstrated that Schwann cells use autophagy to degrade myelin after nerve transection, a process they coined "myelinophagy" (22). These findings were supported in a subsequent publication by Jang et al (20). Given the known association between nutrient restriction and autophagy and the more drastic disruption in distal nerve blood supply caused by transection injury in comparison with crush injury, we wondered if these findings would apply in a nerve crush scenario as well (30).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…GomezSanchez et al recently demonstrated that Schwann cells use autophagy to degrade myelin after nerve transection, a process they coined "myelinophagy" (22). These findings were supported in a subsequent publication by Jang et al (20). Given the known association between nutrient restriction and autophagy and the more drastic disruption in distal nerve blood supply caused by transection injury in comparison with crush injury, we wondered if these findings would apply in a nerve crush scenario as well (30).…”
Section: Discussionmentioning
confidence: 75%
“…To test whether autophagy is necessary for Schwann cell degradation of myelin after nerve crush injury, as has recently been shown after nerve transection, we generated mice in which Schwann cells are unable to perform autophagy due to deletion of essential autophagy protein atg7 (floxed Atg7 × P0 Cre) (20)(21)(22). These mice did not display any obvious behavioral abnormalities before their use for experiments at 8 to 12 wk of age.…”
Section: Assessment Of the Role Of Autophagy In Myelin Debris Clearancementioning
confidence: 99%
“…Although not significant, the proportion of autophagy structures had also decreased in unmyelinated axons while it was increased in Schwann cells at follow-up. Indeed, it has recently been reported that Schwann cells use autophagy as a degradation process (Gomez-Sanchez et al, 2015;Jang et al, 2016). Obviously, the autophagy pathway is affected in both axons and Schwann cells in longterm diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on the up-regulation of the mRNA expression of BDNF at 1, 4, 7, and 14 days post nerve crush injury (Yi et al, 2016). It has been known that after peripheral nerve injury, Schwann cells not only proliferate to form the bands of Bungner, but also produce a range of neurotrophic factors, including BDNF (Frostick et al, 1998; Faroni et al, 2013; Jang et al, 2016). Therefore, the up-regulated BDNF in the distal nerve stump would augment axonal regrowth and promote nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%